A utilização de webquest para o ensino de radioatividade - Vanz, Lucas (2017)
The use of Webquest for the teaching of radioactivity: One of the guiding purpose of the chemistry’ teaching is that students understand the natural phenomena around them and be able to apply the knowledge in a way to facilitate their action into society. In order to make this happen, many strategies are proposed with the aim to improve the teaching/learning process. One of those is the WebQuest (WQ), created by Bernie Dodge in 1995, which has described bya targeted research using the Web as an information resource that have to be converted into knowledge during the process. The constructionism, developed by Papert, emphasize the computer use for construction of knowledge and not only as an information source present intothe network. In addition, stimulate the necessary autonomy for students be able to learn when face news knowledges and do it by themselves. In this way, the principal goal of the present work, which has linked to Theoretical-Methodological Fundamentals for the Mathematics and Science Education research line (PPGECM/UPF), was to elaborate and to apply a WQ, as an educational product, to address radioactivity concepts in a constructivism view. The research was conducted with students of second degree of high school, in a public school located in Marau-RS. The WQ, named “Radioactivity beyond the power plants” was long duration type and divided in four tasks, seeking to discuss, respectively: the basic concepts to comprehend the phenomena, the radioactivity history, the different application of the scientific knowledge involved, and the use of thermonuclear energy. The WQ was developed during two months in the school’ informatics lab. Data collection was realized using opinion questionnaire for students, related the strategy applied, a scientific knowledge evaluation and the notes from the teacher observation. The results indicated, mainly, that the WQ has stimulated the autonomous actions from the students, which allows they realized themselves as being an active part inside the teaching/learning process, improving, in addition, their motivation to learn. It has also noticed an improvement related to scientific concepts understanding.